2020
DOI: 10.1038/s41416-020-01048-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic CD8+ T cells in cancer and cancer immunotherapy

Abstract: The functions of, and interactions between, the innate and adaptive immune systems are vital for anticancer immunity. Cytotoxic T cells expressing cell-surface CD8 are the most powerful effectors in the anticancer immune response and form the backbone of current successful cancer immunotherapies. Immune-checkpoint inhibitors are designed to target immune-inhibitory receptors that function to regulate the immune response, whereas adoptive cell-transfer therapies use CD8+ T cells with genetically modified recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
499
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 929 publications
(627 citation statements)
references
References 103 publications
11
499
2
3
Order By: Relevance
“…The negative association that we identified is in line with the fact that inhibition of endothelial cells favour an anti-tumor immune response (Klein, 2018). As expected, signalling of CD8 + T cells to dendritic cells and cancer cells was identified as strong positive biomarker (in 14 and 10 of the 18 cancer types respectively, Figure 4C), in line with the crucial role these cells play in immune response and mediation of immunotherapy effects (Raskov et al, 2021). Among the top 30 biomarkers, we also found B cells as receiver cells in 6 different CC pairs (with NK cells, Neutrophils, CD8 + T cells, CD4 + T cells, B cells as sender cells and monocytes).…”
Section: Biomarkers Of Immune Response Based On Cell-cell Communicationsupporting
confidence: 85%
“…The negative association that we identified is in line with the fact that inhibition of endothelial cells favour an anti-tumor immune response (Klein, 2018). As expected, signalling of CD8 + T cells to dendritic cells and cancer cells was identified as strong positive biomarker (in 14 and 10 of the 18 cancer types respectively, Figure 4C), in line with the crucial role these cells play in immune response and mediation of immunotherapy effects (Raskov et al, 2021). Among the top 30 biomarkers, we also found B cells as receiver cells in 6 different CC pairs (with NK cells, Neutrophils, CD8 + T cells, CD4 + T cells, B cells as sender cells and monocytes).…”
Section: Biomarkers Of Immune Response Based On Cell-cell Communicationsupporting
confidence: 85%
“…As immunotherapy emerges as an effective therapeutic strategy in cancer, T helper (T H ) cells have received widespread interest owing to their integral role in anti-tumor immune responses as has been demonstrated by diverse pre-clinical and clinical models ( 1 , 2 ). While CD8 + cytotoxic T lymphocyte (CTL) function has been explored extensively in recent years in the context of immunotherapy ( 3 ), research shows the crucial role of CD4 + T H cells and its interaction with dendritic cells (DC) to transmit necessary molecular help that stimulates CTL function ( 4 ). T H 1 and T H 2 subclasses of helper T cells engage in molecular crosstalk with multiple immune signaling pathways and have been investigated for their immunotherapeutic relevance in cancer.…”
Section: Cd4 + T Cells Classificationmentioning
confidence: 99%
“…Those cells are at the highest level responsible for the direct killing of tumor cells through the secretion of cell membrane perforating molecules, i.e., cathepsin C, perforin, granzymes. The second mechanism, induced by CD8+ Tcells, which leads to cell apoptosis, is their expression of the Fas ligand, which, after binding to its receptor on the targeted cell, induces caspases and endonucleases leading to DNA impairment [31]. Previously, it was shown that a low number of CD8+ Tcells correlates with enhanced tumor growth and poor prognosis [32,33].…”
Section: Ido1 and Its Role In Cancer Developmentmentioning
confidence: 99%